Information and Communication Technologies as a Tool of Modern Communication in Organizations and Society - Aleksandra KUZIOR; Anna KOCHMAŃSKA; Izabela MARSZAŁEK-KOTZUR (Communications of International Proceedings, 2021)
The development of modern technologies has also changed the form of communication. Increasingly, the traditional way of direct contact is replaced by inventions of information and communication technologies, which become intermediaries in human relations. The article reflects on the impact of information and communication technologies on the functioning of organizations, society, individuals and the quality of people-to-people relationships. An attempt was made to determine what the communication process is from a management perspective. It describes some of the significant benefits of using ICT and the selected risks that may arise. The importance of developing ethics in the consideration of the essence of ethical communication has been signalled.
Keywords: Communication; ICT; Ethical Communication; Relations Man.